Improving sexual health through partner notification: the LUSTRUM mixed-methods research Programme including RCT of accelerated partner therapy - Estcourt, Claudia S; Mapp, Fiona; Woode Owusu, Melvina; Low, Nicola; Flowers, Paul; Copas, Andrew; Roberts, Tracy E; Mercer, Catherine H; Saunders, John; Nandwani, Rak; Althaus, Christian L; Stirrup, Oliver; et al. (Programme grants for applied research, 2024)
Background Sexually transmitted infections disproportionately affect young people and men who have sex with men. Chlamydia is Britain’s most common sexually transmitted infection. Partner notification is a key intervention to reduce transmission of sexually transmitted infections and human immunodeficiency virus but is hard to implement. Accelerated partner therapy is a promising new approach. Objectives determine the effectiveness, costs and acceptability of accelerated partner therapy for chlamydia in heterosexual people model the cost effectiveness of accelerated partner therapy and impact on chlamydia transmission develop and cost partner notification interventions for men who have sex with men. Design Mixed-methods study to develop a new sex partner classification and optimise accelerated partner therapy; cluster crossover randomised controlled trial of accelerated partner therapy, with process and cost-consequence evaluation; dynamic modelling and health economic evaluation; systematic review of economic studies of partner notification for sexually transmitted infections in men who have sex with men; qualitative research to co-design a novel partner notification intervention for men who have sex with men with bacterial sexually transmitted infections. Settings Sexual health clinics and community services in England and Scotland. Participants Women and men, including men who have sex with men and people with mild learning disabilities. Interventions Accelerated partner therapy offered as an additional partner notification method. Main outcome measures Proportion of index patients with positive repeat chlamydia test (primary outcome); proportion of sex partners treated; costs per major outcome averted and quality-adjusted life-year; predicted chlamydia prevalence; experiences of accelerated partner therapy. Data sources Randomised controlled trial: partnership type, resource use, outcomes, qualitative data: economic analysis, modelling and systematic review: resource use and unit costs from the randomised controlled trial, secondary sources. Results The sex partner classification defined five types. Accelerated partner therapy modifications included simplified self-sampling packs and creation of training films. We created a clinical management and partner notification data collection system. In the randomised controlled trial, all 17 enrolled clinics completed both periods; 1536 patients were enrolled in the intervention phase and 1724 were enrolled in the control phase. Six hundred and sixty-six (43%) of 1536 index patients in the intervention phase and 800 (46%) of 1724 in the control phase were tested for Chlamydia trachomatis at 12–24 weeks after contact tracing consultation; 31 (4.7%) in the intervention phase and 53 (6.6%) in the control phase had a positive Chlamydia trachomatis test result [adjusted odds ratio 0.66 (95% confidence interval 0.41 to 1.04); p = 0.071]. The proportion of index patients with ≥ 1 sex partner treated was 88.0% (775/881) in intervention and 84.6% (760/898) in control phase, adjusted odds ratio 1.27 (95% confidence interval 0.96 to 1.68; p = 0.10). Overall, 293/1536 (19.1%) index patients chose accelerated partner therapy for 305 partners, of which partner types were: committed/established, 166/305 (54.4%); new, 85/305 (27.9%); occasional, 45/305 (14.8%); and one-off, 9/305 (3.0%). Two hundred and forty-eight accepted accelerated partner therapy and 241 partners were sent accelerated partner therapy packs, 120/241 (49.8%) returned chlamydia/gonorrhoea samples (78/119, 65.5%, positive for chlamydia, no result in one), but only 60/241 (24.9%) human immunodeficiency virus and syphilis samples (all negative). The primary outcomes of the randomised trial were not statistically significantly different at the 5% level. However, the economic evaluation found that accelerated partner therapy could be less costly compared with routine care, and mathematical modelling of effects and costs extrapolated beyond the trial end points suggested that accelerated partner therapy could be more effective and less costly than routine care in terms of major outcome averted and quality-adjusted life-years’. Healthcare professionals did not always offer accelerated partner therapy but felt that a clinical management and partner notification data collection system enhanced data recording. Key elements of a multilevel intervention supporting men who have sex with men in partner notification included: modifying the cultural and social context of men who have sex with men communities; improving skills and changing services to facilitate partner notification for one-off partners; and working with dating app providers to explore digital partner notification options. The systematic review found no evaluations of partner notification for men who have sex with men. Modelling of gonorrhoea and human immunodeficiency virus co-infection in men who have sex with men was technically challenging. Limitations In the randomised controlled trial, enrolment, follow-up and repeat infections were lower than expected, so statistical power was lower than anticipated. We were unable to determine whether accelerated partner therapy sped up partner treatment. Mathematical modelling of gonorrhoea/human immunodeficiency virus co-infection in men who have sex with men remained at an experimental stage. It was not feasible to include healthcare professionals in the men who have sex with men intervention development due to the COVID-19 pandemic. Conclusions Although the evidence that the intervention reduces repeat infection was not conclusive, the trial results suggest that accelerated partner therapy can be safely offered as a contact tracing option and is also likely to be cost saving, but is best suited to sex partners with emotional connection to the index patient. The Programme’s findings about classification of sexual partner types can be implemented in sexual health care with auditable outcomes. Future work Further research is needed on how to increase uptake of accelerated partner therapy and increase sexually transmitted infections self-sampling by partners; understand how services can use partnership-type information to improve partner notification, especially for those currently underserved; overcome challenges in modelling sexually transmitted infections and human immunodeficiency virus co-infection in men who have sex with men; develop and evaluate an intervention to optimise partner notification among men who have sex with men, focusing on one-off partnerships. Trial registration This trial is registered as ISRCTN15996256. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research Programme (NIHR award ref: RP-PG-0614-20009) and is published in full in Programme Grants for Applied Research; Vol. 12, No. 2. See the NIHR Funding and Awards website for further award information. Plain language summary We aimed to improve the sexual health of people most impacted by sexually transmitted infections and human immunodeficiency virus (young people and men who have sex with men), by preventing transmission and reducing undiagnosed infection. We focused on partner notification (contact tracing and management), particularly accelerated partner therapy. Our research included: a clinical trial interview/focus group studies literature reviews mathematical modelling and health economic evaluations. Firstly, we improved accelerated partner therapy by finding out what people did/didn’t like about it and which types of sex partners might use it. We included some people with mild learning difficulties to see if they could help us improve accelerated partner therapy for people who might find self-managed care tricky. Then, we measured accelerated partner therapy’s value for money in a large clinical trial in people with chlamydia, Britain’s commonest sexually transmitted infection. Finally, we worked with men who have sex with men, sexual healthcare professionals, public health and health planners to make recommendations for new partner notification methods to suit their needs. We found accelerated partner therapy could be less costly than current practices and likely reduce transmission of chlamydia in the population. Our new classification of partnership types showed that accelerated partner therapy suited ‘emotionally connected’, rather than one-off, partners. These partners are important for controlling onward transmission but are traditionally harder to reach. Findings from our stakeholder event suggest that partner notification approaches for men who have sex with men are likely to work best by involving communities as well as clinics, but we were only able to focus on sexually transmitted infections other than human immunodeficiency virus due to COVID-19 impacts. Future research should aim to improve partner notification for one-off partners, simplify the sexually transmitted infection and human immunodeficiency virus self-testing kits used in accelerated partner therapy, explore the pros and cons of immediate antibiotics, and develop and evaluate a system-wide partner notification approach for men who have sex with men, guided by health economics evaluation. Scientific summary Background Sexually transmitted infection (STI) diagnoses have increased since 2010. Young people and men who have sex with men (MSM) are disproportionately affected. Chlamydia is the most commonly reported STI in Britain. Two-thirds of chlamydia infections are diagnosed in heterosexual people under 25 years, while gonorrhoea, syphilis and human immunodeficiency virus (HIV) infections are more common in MSM. Preventing onward transmission is essential to STI and HIV control. Partner notification (PN), also known as contact tracing and management, is a key intervention in which sex partners (SPs) of people with diagnosed infections are identified, tested and treated. PN also provides